Acute β-adrenoceptor mediated glucose clearance in brown adipose tissue; a distinct pathway independent of functional insulin signaling - Jessica M. Olsen; Alice Åslund; Muhammad Hamza Bokhari; Dana S. Hutchinson; Tore Bengtsson (Elsevier, 2019)
Objective: β-adrenoceptor mediated activation of brown adipose tissue (BAT) has been associated with improvements in metabolic health in models of type 2 diabetes and obesity due to its unique ability to increase whole body energy expenditure, and rate of glucose and free fatty acid disposal. While the thermogenic arm of this phenomenon has been studied in great detail, the underlying mechanisms involved in β-adrenoceptor mediated glucose uptake in BAT are relatively understudied. As β-adrenoceptor agonist administration results in increased hepatic gluconeogenesis that can consequently result in secondary pancreatic insulin release, there is uncertainty regarding the importance of insulin and the subsequent activation of its downstream effectors in mediating β-adrenoceptor stimulated glucose uptake in BAT. Therefore, in this study, we made an effort to discriminate between the two pathways and address whether the insulin signaling pathway is dispensable for the effects of β-adrenoceptor activation on glucose uptake in BAT. Methods: Using a specific inhibitor of phosphoinositide 3-kinase α (PI3Kα), which effectively inhibits the insulin signaling pathway, we examined the effects of various β-adrenoceptor agonists, including the physiological endogenous agonist norepinephrine on glucose uptake and respiration in mouse brown adipocytes in vitro and on glucose clearance in mice in vivo. Results: PI3Kα inhibition in mouse primary brown adipocytes in vitro, did not inhibit β-adrenoceptor stimulated glucose uptake, GLUT1 synthesis, GLUT1 translocation or respiration. Furthermore, β-adrenoceptor mediated glucose clearance in vivo did not require insulin or Akt activation but was attenuated upon administration of a β3-adrenoceptor antagonist. Conclusions: We conclude that the β-adrenergic pathway is still functionally intact upon the inhibition of PI3Kα, showing that the activation of downstream insulin effectors is not required for the acute effects of β-adrenoceptor agonists on glucose homeostasis or thermogenesis. Keywords: Glucose clearance, Brown adipose tissue, GLUT1, Akt, PI3Kα, Insulin, Thermogenesis